Pengaruh Perhatian Orang Tua dan Minat Belajar terhadap Prestasi Belajar Siswa SD Inpres 5/81 Tadang Palie Kecamatan Sibulue Kabupaten Bone - Suci Wirahayu; Muhammad Faisal; Wahira (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study is a quantitative study with a correlational design that aims to determine whether there is a relationship between parental attention and learning interest on student learning achievement of SD Inpres 5/81 Tadang Palie, Sibulue District, Bone Regency. The population in this study were all students of SD Inpres 5/81 Tadang Palie, Sibulue District, Bone Regency, while the sample in this study was 53 students, namely all students of SD Inpres 5/81 Tadang Palie, Sibulue District, Bone Regency. Data collection was carried out by providing questionnaires and documentation. The findings obtained, parental influence with an average of 131.51 and a percentage of 82% is classified as very good, interest in learning with an average of 136.47 and a percentage of 90% is classified as very good, and student learning achievement with an average of 84.11 and a percentage of 84% is classified as very good. The results of this study also show that the t-value (X1 = 1.806 X2 = 4.797) is greater (≥) the t-table value (1.675) at a significance level of 5%. Thus H0 is rejected and H1 is accepted. The results of the study concluded that there is a significant relationship between parental attention and interest in learning on student learning achievement at SD Inpres 5/81 Tadang Palie, Sibulue District, Bone Regency.